1985
DOI: 10.3171/jns.1985.63.3.0390
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I trial of naloxone treatment in acute spinal cord injury

Abstract: Results of a Phase I trial of the opiate antagonist naloxone for treatment of patients with acute spinal cord injury are reported. Naloxone was administered in doses ranging from 5 to 200 mg/sq m (0.14 to 5.4 mg/kg) for up to 48 hours. The patients ranged in age from 16 to 79 years (mean 37 years). Twenty patients received naloxone as a loading dose of 5 to 50 mg/sq m (0.14 to 1.43 mg/kg), followed by a maintenance dose of 20% of the loading dose given as a continuous infusion hourly for 47 hours (Group 1). Ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…This has raised the hope that injured spinal cord is amenable to treatment administered shortly after trauma (6,7). With advances in our understanding of the pathophysiology of spinal cord injury and the molecular events underlying the secondary and progressive injury, several categories of drugs have emerged as promising regimens for reduction of post-traumatic damage and consequent neurological deficit (8).…”
Section: Introductionmentioning
confidence: 99%
“…This has raised the hope that injured spinal cord is amenable to treatment administered shortly after trauma (6,7). With advances in our understanding of the pathophysiology of spinal cord injury and the molecular events underlying the secondary and progressive injury, several categories of drugs have emerged as promising regimens for reduction of post-traumatic damage and consequent neurological deficit (8).…”
Section: Introductionmentioning
confidence: 99%
“…9,40 -42 Furthermore, a phase I study in acute SCI patients showed that the drug was safe in that population. 43 …”
Section: Discovery Of Naloxone Therapy For Acute Scimentioning
confidence: 99%
“…Moreover, it reverses the spinal shock and improves the blood flow to the spinal cord [51,52] . It was extensively studied in the early 1980s and in the 1980s the opioid antagonist naloxone was examined in a Phase I SCI trial in humans [53][54][55] . However, beneficial effects of naloxone that were thought to be due to antagonization of the increase of the endogenous opiates observed after SCI were not confirmed.…”
Section: Opioid Receptor Antagonistsmentioning
confidence: 99%